Electrodiagnostic assessment of autonomic nervous system in diabetic autonomic neuropathy: Case series in 72 diabetes patients - Suchitra Dube; Sandip M. Hulke; Santosh L. Wakode; Sagar Khadanga (Journal of Family Medicine and Primary Care)
Diabetic autonomic neuropathy is one of the most common complications of diabetes which is asymptomatic in early stage. Hence HRV and AFT are performed to detect and prevent its progression to advanced stages. To discuss the HRV and AFT findings in diabetic patients. An observational study was conducted in Physiology department of AIIMS, Bhopal in collaboration with the Medicine department of the institute. Seventy-two diagnosed Type-2 Diabetes mellitus patients were examined using POWER LAB AND LAB CHART 8 BY AD INSTRUMENT: For recording heart rate variability (HRV) and Ewing’s battery of tests: For Autonomic function testing. Microsoft Excel was utilized for data compilation and for result analysis. In the present study, based on HRV parameters sympathetic involvement was seen in 39% while parasympathetic involvement was seen in 15% of patients. Balanced state was observed in 46% of the patients. Based on AFT battery, normal early involvement was observed in 62% of the patients while definite and severe involvement was observed in 14 and 24%, respectively. Diabetic autonomic neuropathy was observed in 72% of the patients based on HRV and AFT testing. In severe involvement, orthostatic hypotension was seen. Severe involvement was observed in 24% of the patients in present study. Involvement of the vagal parasympathetic component of ANS was obvious evidenced by increase in resting heart rate, decrease in Valsalva ratio, E/I index, and standing ratio. Diabetic autonomic neuropathy was observed in majority of patients with normal early involvement seen predominantly and though majority of them were in balanced state, sympathetic involvement was also seen at large. HRV studies depicted a decrease of total power, decreased low frequency (LF) and high frequency (HF) with LF/HF and SD1/SD2 ratios depicting sympathetic involvement.